Restructuring Islamic Social Finance Ecosystem on Standardization of Waqf in Indonesia: Platform Digitized - Aisyah, Siti Nur; Muiz, Abdul (Talaa : Journal of Islamic Finance, 2022)
The emergence of waqf forum applications raises an issue that has to be immediately resolved, where the management of public funds requires sufficient transparency and the efficient access to it to continue to attract public attention. This study will discuss the extent to which digital actors manage waqf are in accordance with Waqf Core Principle (WCP). With the presence of WCP as part of the guide for the course of managerial principles, it should be the main consideration for every manager of this waqf platform. The availability of the information for each platform and website mentioned branding and the source of information. From the 29 cores of WCP and the 5 selected platforms; Dompet Dhuafa and Rumah Zakat have been approved and standardized by WCP. It does not mean that Global Zakat is not proper enough to be a waqf organization, it is only a matter of the lack of information provided by Global Wakaf. For Kitabisa and Ammana, they do not need to be standardized by BWI or WCP as they are intermediaries’ platforms instead of waqf platforms. The growing number of Cash Waqf will ultimately improve financial inclusion in Indonesia as one of the government’s goals.